Analisis Pengaruh Substitusi Parsial Semen Dan Agregat Halus Menggunakan Fly Ash Dan Cangkang Kerang Darah Terhadap Kuat Tekan Beton - Agyanata Tua Munthe; Trisna Dewangga (Universitas Islam Raden Rahmat, Malang, 2024)
The construction industry demands more concrete, resulting in increased mining of concrete components. Consequently, the availability of natural resources to meet the demand for concrete is decreasing. Therefore, there are various ways to create new concrete mixtures using waste materials. In this research, fly ash and blood cockle shells were used as partial replacements for cement and fine aggregates, as these two waste materials have not been properly utilized. Test results over 28 consecutive days showed variations in normal concrete of 5%, BKF 7.5%, BKF 7.5%, and BKF 10% with 25.84 MPa, 29.28 MPa, 27.15 MPa, and 24.92 MPa, respectively. The consecutive slump test results for normal concrete variations of 5%, BKF 7.5%, BKF 7.5%, and BKF 10% were 80 millimeters, 85 millimeters, 100 millimeters, and 76 millimeters, respectively. The consecutive slump test results for normal concrete variations of 5%, BKF 7.5%, BKF 7.5%, and BKF 10% were 80 millimeters, 85 millimeters, 100 millimeters, and 76 millimeters. The water absorption test results for normal concrete of 5%, BKF 7.5%, and BKF 10% were 2.81%, 2.85%, 2.79%, and 2.78%, respectively, over 28 consecutive days.